Warm temperature during floral bud transition turns off EjTFL1 gene expression and promotes flowering in Loquat (Eriobotrya japonica Lindl.) - Reig, Carmina (Plant science : an international journal of experimental plant biology, 2023)
Copyright © 2023 The Authors. Published by Elsevier B.V. All rights reserved.